Effects of dissipation on the time evolution of coherence and entanglement of a two-quantum dot system in a microcavity (2010)
ABSTRACT: The effects of dissipation on a system composed by two quantum-dot qubits interacting with a single mode of light in a microcavity are studied by computing the time evolution of mixedness and entanglement of the qubits and the second order correlation function of the field.